Project Outline: Wearing Our Stories - Latino costume, adorment and identity - Cardona, Rudy
Rudy Cardona's project outline for a documentary on how Chicanos make cultural statements by the clothing they wear. Has a list of possible subjects to be interviewed, including Lupe Anguiano.